Brahmand world defence update 2023 (New Delhi Pentagon, 2023)
Brahmand World Defence Update 2023 aims at providing a comprehensive assessment of the present time global military order with a focus on each nation's military capabilities, new arms acquisitions and defence spending. The 12th edition of the yearbook featuring a new chapter on Electronic Warfare (EW) Systems of China, India, Israel, Russia, the UK and USA, promises to add fresh impetus to the book by focusing on major countries' various electronic warfare systems and the latest advances of the systems under development. The yearbook also contains the up-to-date information on defence capabilities of 113 countries and has highlighted 33 important countries along with their geopolitical importance, internal and external conflict areas, threat perspectives, strategic relations, multilateral alliances, defence capabilities including strategic forces and defence deals.
Keywords: Security Sector; Military Science; Military Relation- India